Research and Evaluation of Methods for Determining Deformation Modulus of Road Subgrade and Frost Blanket Course - Lina Bertulienė; Alfredas Laurinavičius (The Baltic Journal of Road and Bridge Engineering)
Pavement structural strength is one of the main indices determining pavement ability to carry traffic loads. In determining deformation modulus of pavement structure the static and dynamic non-destructive methods are worldwide used, however, in many countries, when designing and building pavement structures, the strength of road pavement structure is characterized by a static deformation modulus. In order to find out and compare the accuracy of testing results of using the static and dynamic methods, in 2007 the Automobile Road Research Laboratory of the Vilnius Gediminas Technical University carried out the comparable measurements of the subgrade and frost blanket course of a test road section with the help of four measuring devices. Measurements were carried out with each device on the same layer of the road pavement structure. Based on the study findings, the dependence of device measuring results on the subgrade and frost blanket course is presented.